A Study Protocol to Determine the Effect of a Mediterranean Diet Intervention on Improving Gastrointestinal Function in Parkinson's Disease. (29th May 2020) - Rusch, Carley; Beke, Matthew; Nieves, Carmelo; Ukhanova, Maria; Mai, Volker; Ramirez-Zamora, Adolfo; Hess, Christopher; Langkamp-Henken, Bobbi
Abstract: Objectives: Constipation is a common and debilitating nonmotor symptom of Parkinson's disease (PD) that is poorly understood and has limited treatment options. A preliminary pilot study conducted at our center suggests that a Mediterranean diet, which emphasizes foods rich in fermentable fibers and antioxidants, can reduce symptoms of constipation in patients with PD, but may also result in unintended reductions in body weight. This may potentially attenuate the benefit of this dietary intervention. The primary outcome of this project is to test the efficacy of a Mediterranean diet intervention on improving the clinical symptoms of constipation in PD. Secondary outcomes will determine the effect of this intervention on body composition, fecal microbial communities and markers of intestinal inflammation and permeability. Methods: This is a 10-week, randomized, controlled, parallel study. Participants with PD (diagnosed by a movement disorder neurologist) who have symptoms of constipation and do not follow a Mediterranean diet will be recruited (n = 42). During the 2-week run-in period, participants will undergo neurological, nutritional, and body composition assessments. Urine and stool samples to assess intestinal permeability (urine sugar probe test), inflammation and microbial communities will be collected. Participants will then be randomized to follow the Mediterranean diet or to maintain their habitual diet for 8 weeks. A study dietitian will provide in-person dietary instruction and weekly follow-up via telephone to both groups to support diet adherence and monitor changes in weight and adverse events. Throughout the study, questionnaires will assess dietary intake and gastrointestinal function including laxative usage. Measurements completed at baseline will be repeated at 4 and 8 weeks of the intervention. Results: N/A Conclusions: We hypothesize that a Mediterranean diet intervention administered by a registered dietitian/nutritionist will result in dietary changes that improve constipation symptoms, reduce intestinal permeability and inflammation, and favor beneficial microbial communities without producing unintended effects on body mass. Funding Sources: University of Florida Moonshot Initiative.